Mekanisme Teoritis Pembentukan Senyawa Siklik Hidrokarbon dari Reaksi C4H5 dan C4H2 - Indarto, Antonius; Handojo, Lienda (Indonesian Journal of Chemical Research, 2020)
Acetylene and polyyne are intermediates in the formation of Polycyclic Aromatic Hydrocarbons (PAHs) and soot in combustion or pyrolysis. PAH formation from acetylene is known as the most adopted pathway because it has a low reaction energy. Another mechanism for the formation of PAH is a mechanism that involves polyyne or known as a radical pathway, proposed by Krestinin. This pathway involves the reaction of alkyne + alkenes which results in the addition of radical sites to the molecular structure. In this study, the two reaction mechanisms will be compared. Electronic features and energy requirements of the reaction process will be evaluated using molecular computational studies based on electron density (DFT). In combustion conditions (high temperature), the formation of radical sites requires relatively little energy, with a range of 2-5 kcal/mol. This is very different when compared to the energy profile for the same reaction at room temperature. From this study, it can be concluded that the mechanism of radical growth has the potential to occur in combustion reactions.Polycyclic aromatic hydrocarbons, radical growth, combustion, polyyne.